Hubungan Status Gizi dengan Perkembangan Anak Usia 3-5 Tahun di Puskesmas Citangkil II Kota Cilegon - Herni Febriawati; Trisonjaya Trisonjaya; Rangga Saputra; Nurry Ayuningtyas (Universitas Malahayati Lampung, 2023)
ABSTRACT Optimal development in toddlers needs to be supported by intake of nutrients and daily food in the right amount and good quality. Malnutrition in infancy can result in losses that cannot be repaired or replaced at a later date. To determine the relationship between nutritional status and motor development in children aged 3-5 years. Correlational quantitative research with cross sectional design. The number of samples is 110 children aged 3-5 years taken using purposive sampling technique. Results: The results of the univariate analysis showed that most of the children aged 3-5 years at the Citangkil II Health Center in Cilegon City had good nutritional status (72.6%) and most of them had development according to their age (61.8%). The results of the bivariate analysis obtained a p value: 0.000, so it was stated that nutritional status had a relationship with the development of children aged 3-5 years. There is a relationship between nutritional status and the development of children aged 3-5 years at Citangkil II Health Center, Cilegon City. Keywords: Toddler, Nutritional Status, Development ABSTRAK Perkembangan yang optimal pada balita perlu didukung oleh asupan zat gizi dan makanan sehari-hari dalam jumlah yang tepat dan kualitas yang baik. Kekurangan gizi pada masa balita dapat mengakibatkan kerugian yang tidak dapat diperbaiki atau digantikan di kemudian hari. Untuk mengetahui hubungan status gizi dengan perkembangan anak usia 3-5 tahun. Penelitian kuantitatif korelasional dengan desain cross sectional. Jumlah sampel adalah 110 anak usia 3-5 tahun diambil dengan menggunakan teknik purposive sampling. Hasil analisis univariat menunjukkan anak usia 3-5 tahun di Puskesmas Citangkil II Kota Cilegon sebagian besar memiliki status gizi baik (72,6%) dan sebagian besar memiliki perkembangan sesuai dengan umur (61,8%). Hasil analisis bivariat diperoleh p value: 0,000, sehingga dinyatakan bahwa status gizi memiliki hubungan dengan perkembangan anak usia 3-5 tahun. Ada hubungan antara statsus gizi dengan perkembangan anak usia 3-5 tahun di Puskesmas Citangkil II Kota Cilegon. Kata Kunci: Balita, Status Gizi, Perkembangan